Analysis Of Macro Nutrients Of Chicken Manure Decomposed Bytrichoderma Viridemushrooms With Different Storage Lengths - Erwin Harahap, Darmadi; Hardianti Wahyuni, Siti; Darwis, Muhammad; Fajrin Harahap, Muharram; Maulana, Mizan (International Journal of Science and Environment (IJSE), 2023)
Trichoderma spp. It is an antagonistic fungus that is very important for biodiversity control. This research was conducted at the Laboratory of the Faculty of Agriculture, Universitas Graha Nusantara Padangsidimpuan, with a height of + 480 m above sea level, in August to September 2018. This study only analyzed the nutrient content contained in the finished compost consisting of five compost treatments, namely: A0 = Chicken manure decomposed by T.viride for 0 weeks, A1 = chicken manure decomposed by T. viride for 1 week, A2 = chicken manure decomposed by T. viride for 2 weeks, A3 = chicken manure decomposed by T. viride for 3 weeks, A4 = chicken manure decomposed by T. viride for 4 weeks. Of the five compost treatments then analyzed the nutrient content which includes N, P, K Total in the Laboratory of Soil Science ANDALAS Padang West Sumatra. The results showed that based on the results of laboratory analysis it can be known that compost with the addition of good trichodermaviride decomposer is good by 4 weeks of storage (A4) i.e. organic B = 45.70 %, organic C = 91.03 , Ratio C / N = 11. 13 %, N Total = 3.51 %, P Total = 3.41 % , K Total = 1.58 %.